The Philippines’ antidrug campaign: Spatial and temporal patterns of killings linked to drugs - Atun, Jenna Mae L (Archīum Ateneo, 2019)
Background As soon as President Rodrigo Duterte assumed office in 2016, the Philippine government launched a nationwide antidrug campaign based on enforcement-led anti-illegal drugs policies primarily implemented by the national police. This was followed by a spate of killings resulting from both acknowledged police operations and by unidentified assailants. This study assembles a victim-level dataset of drug-related killings covered by the media during the Philippine government’s antidrug campaign, and presents a spatial and temporal analysis of the killings. Methods The dataset covers information on 5021 people killed from May 10, 2016 to September 29, 2017. Data collected systematically through online search procedures and existing listings of media organizations detailing information about incidences of drug-related police operations and drug-related killings in 'vigilante-style' manner reveal patterns for who were being killed, where, and how. Results Over half of the killings were due to acknowledged police operations, and the rest were targeted in so-called 'vigilante-style' killings. The first three months after Mr. Duterte was sworn in were the deadliest months. Those who were killed were mostly low-level drug suspects. The analysis of temporal pattern reveals the scale of killings in the country, with rapid escalation starting in July 2016 and lasting throughout the rest of that year. Observable declines occurred during periods when the 'drug war' was suspended and operations were moved to a non-police enforcement unit and rose again when police were brought back into operations. The spatial analysis indicates a large concentration of deaths in the National Capital Region (40%) compared to the rest of the country with wide variations across cities and regions. Conclusions Overall, the Philippine 'drug war' exhibits similarities with violent wars on drugs waged in other countries such as Thailand, with heavily police-led interventions leading to fatalities in the thousands over a span of under two years. Findings of this study point to important policy adjustments that need to be made, including the role that local governments play in drug policy implementation, the disproportionate negative impacts of enforcement-led policies against drugs on urban and poor areas, the targeting of low-level suspected drug dealers and users, and the importance of proper data monitoring and transparency by the government to inform policy adjustments in the face of high costs to human life. We also discuss the importance of independent monitoring systems when the government reports conflicting information.